Pengaruh Brand Symbolism dan Promosi terhadap Purchase Intention yang Dimediasi Brand Identification - Muna, Nilna; Dhirgayusa, I Gede Perdana; Martini, I. A. Oka; Laksmi P. , Kadek Wulandari (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The retail industry in Indonesia faces intense competition due to rapid development of digital technology and e-commerce, requiring companies to strengthen marketing strategies relevant to changes in consumer behavior. Matahari Department Store, as one of the largest retailers, has experienced fluctuating performance, reflected in the decline in the number of outlets and unstable sales trends in recent years. This condition demonstrates the importance of evaluating factors that influence consumer purchase intention, particularly brand symbolism and promotion, as well as the role of brand identification as mediating variable. This study aims to analyze the influence of brand symbolism and promotion on purchase intention, both directly and through the mediation of brand identification, among Matahari consumers in Denpasar City. The study used quantitative approach with a sample of 128 respondents selected using a purposive sampling technique according to established criteria. Data processing was carried out using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. The results showed that brand symbolism and promotion had a positive and significant effect on brand identification. In addition, brand symbolism, promotion, and brand identification were proven to have a positive effect on purchase intention. Other findings revealed that brand identification acts as a significant partial mediator in the relationship between brand symbolism and promotion on purchase intention. Overall, this study confirms that strengthening the symbolic meaning of a brand, effective promotional support, and building strong brand identification are important factors in increasing consumer purchase intentions in the modern retail industry such as Matahari Department Store.